Acute Influenza Virus-Associated Encephalitis and Other Neurological Complications in Severe Hospitalized Laboratory-Confirmed Influenza Cases—Catalonia 2010–2020 - Pilar Ciruela; Nuria Soldevila; Nuria Torner; Luca Basile; Maria del Mar Mosquera; M. Angeles Marcos; Anna Martínez; Mireia Jané; Cristina Rius; Angela Domínguez; the Working Group for the Catalan Influenza and Severe Acute Respiratory Infection Sentinel Surveillance Network (PIDIRAC) (Pathogens)
Neurological complications associated with influenza (NCIs) are rare events in adults. Influenza-associated encephalopathy is one of the most severe and frequently reported NCIs. The aim of this study is to describe the frequency and characteristics of NCIs in adults during 10 post-2009 pandemic influenza seasons. Data were obtained from the registry of influenza cases admitted to hospitals of the PIDIRAC network for the surveillance of severe hospitalized laboratory-confirmed influenza (SHLCI) cases in Catalonia from October 2010 to March 2020. The variables analyzed were NCI, age, antiviral treatment, vaccination status, and outcome at discharge. During the study period, 9 (1.5‰) of 5931 SHLCI cases presented NCI. Five (55.6%) had influenza A and four (44.4%) had influenza B. Median age was 62 (17–67) years. One case had been vaccinated, all had received antiviral treatment, and five required ICU admission. The mean length of stay was 25.6 days (SD 25.8). Encephalitis was the most frequent complication, occurring in six cases (66.7%). Of these, three cases (50%) were caused by influenza A (two AH1N1pdm09 strains and one AH3N2). The high frequency of influenza-associated encephalitis caused by both type A and B influenza viruses suggests that both should be considered as potential etiologic factors for encephalopathy and other neurological diseases in adults. This recommendation would allow for the prompt antiviral treatment and prevention of severe outcomes.